IMPLEMENTATION OF THE SPACED REPETITION TECHNIQUE BASED ON THE SYNAPSE MOBILE APPLICATION FOR OPTIMIZING QURAN MEMORIZATION AT MADRASAH ALIYAH DDI BANUA - Hidayat, Muhammad Irwan; Aziz, St Aminah; Ahdar; Muhdin; Idris, Mahsyar (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to analyze the effectiveness of applying the spaced repetition technique through the Synapse mobile application in optimizing Qur’an memorization at Madrasah Aliyah DDI Banua. The research employed a mixed-methods approach with a sequential explanatory design. A total of 60 students were purposively selected, and data were collected through memorization tests, motivation questionnaires, interviews, and observations. The findings revealed a significant improvement in students’ memorization retention, as indicated by the comparison between pre-test and post-test scores. Moreover, students’ learning motivation increased due to the application’s interactive features and gamification elements, while time efficiency was achieved through a more flexible memorization schedule. These results are consistent with cognitive theory on memory retention and support the concept of mobile learning in expanding the scope of learning beyond formal settings. Therefore, the Synapse application effectively enhances memory retention, learning motivation, and time efficiency in Qur’an memorization.